Towing Car Booking System Using Android and Web Based Application - Septian Hadinata; Elvania Ayu Muhsina; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2015)
To deal with broken cars on the road, a towing car booking system using android operating system is made. By using GIS (Geographic Information System) for the development, ensuring the location of the customer become easier. Meanwhile, the towing car booking management application is developed using PHP programming language. Data management in this application uses the MySQL database engine. While GPRS (General Pocket Radio System) channel is used for sending customer data. This application is designed using the UML (Unified Modeling Language) which is suitable for modeling applications developed with object-oriented language (OOP). In this towing car booking application, the android application acts as a client while the web application as a server which is used by the operator of the towing car company in managing data orders from customers. This application has successfully designed and implemented, it is concluded that the system built has benefits for driver, the system interface built has a simple display and easy to use by users, and the system has running well functionality. Therefore, it can be a reference for android application developers who have integration concept between android and web applications.